Oral Cancer Immunotherapy through a Simvastatin‐Loaded Colloidal Dispersion System for the Generation of Sustained Antitumor Immunity. Issue 8 (26th March 2021) - Kim, Seong A; Nam, Gi‐hoon; Bae, Young Rang; Jha, Saurav Kumar; Kim, Seohyun; Choi, Yoonjeong; Lee, Yeji; Kwon, Minsu; Jeong, Cheolhyun; Byun, Youngro; Park, Jin Woo; Kim, In‐San
Abstract: Statins exhibit anticancer pleiotropic effects, such as the induction tumor‐specific apoptosis and the promotion antitumor immunity. However, due to low bioavailability, high doses are required to trigger such antitumor effects. In this study, an oral delivery system to improve bioavailability of simvastatin (SIMVA) is prepared and its application in combination with an oral anticancer formulation is investigated. A colloidal dispersion (CD) of SIMVA is prepared using N α ‐deoxycholyl‐l ‐lysyl‐methylester (DL) to enhance a solubility and permeation (SIMVA/DL‐CD). Preparation of SIMVA/DL‐CD markedly increases the solubility and in vitro artificial membrane permeability of SIMVA by 291‐ and 4.68‐fold, respectively, compared to SIMVA in 5% dimethyl sulfoxide. The oral absorption of SIMVA/DL‐CD (20 mg kg −1 SIMVA) is significantly enhanced and its oral bioavailability is tenfold higher compared to that of free SIMVA. An in vivo study in CT26 tumor‐bearing mice receiving SIMVA/DL‐CD reveals substantial tumor growth suppression through upregulated anticancer immunity. In particular, the combination of oral SIMVA/DL‐CD and oxaliplatin powder formulation elicits considerable tumor‐suppressive effects and CD8 + T cell immunity. Furthermore, this combination therapy sensitizes antiprogramed cell death protein‐1 monoclonal antibody‐resistant tumors to checkpoint blockade. The current findings highlight the therapeutic potential of oral SIMVA/DL‐CD as an effective anticancer immunotherapy. Abstract : Simvastatin‐loaded colloidal dispersion (SIMVA/DL ( N α ‐deoxycholyl‐l ‐lysyl‐methylester)‐CD) shows increased solubility, permeability, and oral bioavailability of water‐insoluble simvastatin (SIMVA). SIMVA/DL‐CD enhances CD8 + T cell immunity by potentiating its functionality. A combined therapy with oxaliplatin‐loaded solid oral formulation induces immunogenic cell death that can prime dendritic cells in immune checkpoint blockade‐resistance CT26 murine colon cancer, which sensitized the CT26 cancer to programmed cell death protein‐1 blockade.